An ink surgical marker pen is damagingto tendon cells. Issue 3 (March 2012) - Franklin, S. L.; Jayadev, C.; Poulsen, R.; Hulley, P.; Price, A.
Abstract : Objectives: Surgical marking during tendon surgery is often used for technicaland teaching purposes. This study investigates the effect of a gentianviolet ink marker pen, a common surgical marker, on the viabilityof the tissue and cells of tendon. Methods: In vitro cell and tissue methods were used totest the viability of human hamstring explants and the migrating tenocytesin the presence of the gentian violet ink. Results: The outcome of this study was that a constituent of the surgicalmarker pen causes cell and tissue death in culture, implying thesame would occur in vivo . Conclusions: This is a cause for concern when marking tendon during surgicalprocedures, as it may compromise healing and repair and potentiallycontribute to a poor outcome. The authors suggest that an alternativesurgical marking procedure should be found, or that all marker pensshould undergo testing on human tendon tissue in vitro priorto use.